Effect of Foot Reflexology on Anxiety in Women with Breast Cancer: A Randomized-controlled Trial - Mohadeseh Rezaei; Vahid Naseri-Salahshour; Fatemeh Rafiei; Fatolah Mohagheghi; Mahbobeh Sajadi (Mashhad University of Medical Sciences, 2022)
Background: Anxiety is considered a common problem in women with breast cancer, and non-pharmacological interventions, such as reflexology, can contribute towards controlling.Aim: This study aimed to determine the effect of foot reflexology on anxiety in women with breast cancer.Method: In this randomized-controlled clinical trial, 66 women with breast cancer referred to Ayatullah Khansari Hospital, Arak, Iran, were selected based on the inclusion criteria by convenience sampling method and randomly assigned into intervention and control groups using a randomized block allocation method. In the intervention group, reflexology was then conducted by a trained nurse in the oncology department in a two-point morning and afternoon session for 40 min on the thumb and solar plexus of the feet. However, the control group did not receive any intervention and the Spielberger State-Trait Anxiety Inventory was completed again by the patients.Results: The mean anxiety scores before reflexology were 48.27±4.95 and 49.72±4.18 in the intervention and control groups, respectively (P=0.202). Furthermore, the mean anxiety scores in the intervention and control group after reflexology were obtained at 47.03±4.14 and 49.71±4.28, respectively.Implications for Practice: As reflexology did not affect the anxiety of women with breast cancer, this method can be combined with other non-pharmacological interventions to control anxiety in women with this complication; however, it should not be utilized alone in the clinic to manage anxiety. Further studies are recommended to be conducted with larger sample sizes and extended periods on anxiety and mental health disorders in these women.